PENGARUH BUDAYA TERHADAP KINERJA PEREKONOMIAN - Pratikto, Adji (Buletin Studi Ekonomi; Vol 17.No.2.Agustus 2012 (PP.99-225), 2012)
Abstact: Cultural Influence On Economic Performances. In the analysis of economics, cultural influences on the performance of an economy still an assumption of binding, due to the difficulty of economics to understand it. It is difficult to quantify the variables associated with culture, and also because the culture itself is embedded everywhere as in tastes, habits and so forth. But in its development, economists began to recognize that culture has an important role in supporting the performance of the economy, because it is associated with the formation of trust within the group, thereby reducing transaction costs
Keywords: budaya, kinerja perekonomian, trust, biaya transaksi, dan pendidikan